ROLE OF INTRAVITREAL RANIBIZUMAB IN TREATING THE DIABETES MELLITUS TYPE-2 PATIENTS WITH SUBFOVEAL CHOROIDAL THICKNESS AND DIMINISHED VISUAL ACUITY - SIVA SANKAR PR,; PRASAD YMS, (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study was conducted with the objective to measure the Subfoveal Choroid thickness and correlate it with the diminished visual acuity in patients with Diabetes Mellitus Type 2, who develop macular edema and to study the effect of Intravitreal injections of Ranibizumab during follow up. Methods: A cross sectional, interventional study conducted in 52 patients with uncontrolled Diabetes Mellitus Type-2 with macular edema by measuring the Subfoveal Choroid thickness with the help of manual caliper function present in the Heidelberg Spectralis OCT program. Patients with SFCT less than 450 microns were included. The SFCT and the corresponding visual acuity were measured before and after Intravitreal Ranibizumab injections 1.25mg (0.05mL) at monthly intervals for 3 months and correlated with age, gender, and choroid thickness. Results: Out of 52 patients there were 31 (59.61%) females and 21 (40.38%) males. 50% of the patients were aged between 50 and 60 years and 50% patients were aged between 60 and 70 years. The patients responding to the Intravitreal injections in terms of best-corrected visual acuity (BCVA) between the reinjection and post-injection were found to be statistically important (p=0.001). The subfoveal Choroidal thickness (SFCT) variations, before and after injections were found to be statistically significant at the end of 3 months (p<0.05). Conclusions: Injection Ranibizumab was found to have a significant role in the reduction of average SFCT and in addition clear evidence of improved BCVA.